Assessment of the distance between root apices of mandibular posterior teeth and the mandibular canal: A cone beam computed tomographic study in an Indian subpopulation - P. Mondal; R. Nag; J. Das; K. Mandal; T. Paul; S. Das; L. B. Murmu; K. K. Saha (Эндодонтия Today, 2025)
INTRODUCTION. The mandibular canal (MC) is a critical anatomical structure that houses the inferior alveolar nerve (IAN). Its juxtaposition to the apices of the mandibular posterior teeth has significant clinical consequences for dental implant placement and endodontic procedures. Despite its importance, limited data exist on its anatomical variations in the Eastern Indian population.AIM. This study aimed to evaluate the distances between the MC and root apices of mandibular premolars and molars, considering age and sex differences.MATERIALS AND METHODS. This retrospective Cone Beam Computed Tomography (CBCT)-based observational study included 111 participants aged 18–50 years. Distances from the MC to the root apices of mandibular premolars and molars were measured using CBCT scans. Spearman’s correlation test was employed to assess the relationship between age and the measured distances. Distances between genders were compared using the Mann-Whitney test, and Friedman’s ANOVA analyzed intragroup variations. An alpha level of five percent was considered as a level of statistical significance.RESULTS. A positive correlation was observed between age and the distance from the MC to root tips. Males exhibited greater distances compared to females. Significant pairwise comparisons showed differences between the second premolar and both roots of the first and second molars. No discernible differences were found between sides (right versus left). Notably, molar root tips, especially second molars were closest to the MC, with distal roots showing the greatest variability.CONCLUSIONS. The study emphasizes the necessity of precise preoperative evaluations in endodontics and implantology to reduce the incidence of IAN injuries by highlighting age-related increases in the MC to tooth root apices distances, especially in males.